2021
DOI: 10.1029/2020gl091152
|View full text |Cite
|
Sign up to set email alerts
|

Do CMIP6 Climate Models Simulate Global or Regional Compound Events Skillfully?

Abstract: Global climate models are used to simulate climate and weather extremes, including extreme rainfall, high and low temperatures, droughts, and winds. Analyses of observations, historical simulations, and projections of extremes (Alexander, 2016; Bindoff et al., 2013; Sillman et al., 2013) have provided major advances in understanding how the statistics of extremes respond to natural variability and global warming. Many analyses of extremes focus on single hazards, such as how hot is the hottest day each year, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 40 publications
(78 reference statements)
1
65
0
Order By: Relevance
“…• projecting the risk of compound extremes for different levels of future warming (Zscheischler et al, 2018;Wang et al, 2020); • evaluating the impacts of the compound extremes on natural and built environments (AghaKouchak et al, 2020;Zhang and Najafi, 2020); • developing adaptation measures to the changing risk of compound extremes (Weber et al, 2020;Clarke et al, 2021); • enhancing subseasonal-to-seasonal prediction of these extremes (Zamora et al, 2021;Zou, 2021); • improving the representation and evaluation of compound extremes in fully-coupled climate models (Ridder et al, 2021;Zscheischler et al, 2021) and developing multivariate bias correction for these models (Vezzoli et al, 2017;Zscheischler et al, 2019); • applying machine learning to understand these extremes Zou, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…• projecting the risk of compound extremes for different levels of future warming (Zscheischler et al, 2018;Wang et al, 2020); • evaluating the impacts of the compound extremes on natural and built environments (AghaKouchak et al, 2020;Zhang and Najafi, 2020); • developing adaptation measures to the changing risk of compound extremes (Weber et al, 2020;Clarke et al, 2021); • enhancing subseasonal-to-seasonal prediction of these extremes (Zamora et al, 2021;Zou, 2021); • improving the representation and evaluation of compound extremes in fully-coupled climate models (Ridder et al, 2021;Zscheischler et al, 2021) and developing multivariate bias correction for these models (Vezzoli et al, 2017;Zscheischler et al, 2019); • applying machine learning to understand these extremes Zou, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…While regional climate models are extremely useful in resolving land conditions (Fischer et al, 2007;Stéfanon et al, 2014;Keune et al, 2016;Sillmann et al, 2017), global climate models are commonly used to assess changes in land conditions on extreme weather (e.g., drought and heat wave) (Hauser et al, 2016;Kala et al, 2016;Rasmijn et al, 2018). The models in the Coupled Model Intercomparison Project Phase 6 (CMIP6) exhibit some skill in simulating the co-occurrence of hot and dry compound events in North America and Europe (Ridder et al, 2021). Because the numerical models' outputs are limited by the climatological biases, univariate and multivariate bias correction methods have been used to correct the biases, and thus improving the performance and usability of the models (Maraun, 2016;Vezzoli et al, 2017;Vrac, 2018;Zscheischler et al, 2018;François et al, 2020).…”
Section: Numerical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted by other CMIP6 model simulation evaluation studies (e.g., Akinsanola et al, 2021;Ngoma et al, 2021), CMIP6 model simulations generally show biases in representing regional precipitation patterns. For the current study domain, biases shown could be resulting from, among other factors, local climate and mesoscale convective systems (Ridder et al, 2021) and the general complexity of East Africa's large-scale controlled climate (Li et al, 2016;Nicholson, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the lake is notorious with intense lightning and convective storms (Albrecht et al, 2016) and its severe weather and water currents have been linked to boat accidents causing approximately 5000 deaths on the lake annually (Barnett, 2013;Cannon et al, 2014). However, the understanding of weather and climate dynamics in the LVB remains limited due to, in part, the inability of current climate models to adequately represent weather and climate dynamics over Lake Victoria (e.g., Finney et al, 2020;Ridder et al, 2021;Vanderkelen et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%